HADIS-HADIS TENTANG METODE PENDIDIKAN - Syahrin Pasaribu (STIT Al-Ittihadiyah Labuhanbatu Utara, 2018)
The success of instilling spiritual values (faith and devotion to God Almighty.) in a self learner, is associated with a factor of education system, namely the method of education educators in conveying messages ilahiyah, because with the right method, the subject matter will be easily controlled by the learners. In Islamic education, the educational methods used need to be able to do a thorough approach towards human beings, including the physical and spiritual dimensions (outward and batiniah), although there is no one type of method the most appropriate education achieving goals with all the circumstances. Rasul saw. Since the beginning of the education methods in exemplifying the right against his companions. Learning strategies which he did very accurate in conveying the teachings of Islam. Rasul saw. very attentive to the situation, conditions and character of a person, so that Islamic values can be transferred properly. The Prophet. also really understand the instinct and the condition of each person, so that he is able to make them good, and joy as well as spiritual, he always invites people to approach Almighty God. and his jurisprudence. This paper will present the Hadith-Hadith of the Prophet. about the methods of education implemented the Messenger. Hadith-Hadith about the methods of education implemented the Apostle saw, include; example method, the method of gentle/affection, the deductive method, method of the parable, allegory method, the method gives the ease of comparison, the method, the method of questioning, repetition method, method demonstrations, experimental methods, methods of solving the problem, method, method of discussion of praise/give the joy, the method of awarding the penalty